Hubungan Pemberian Susu Formula Dengan Kejadian Diare Pada Bayi di Ruang Dahlia RSUD Dr. H. Soewondo Kendal - Tri Sakti Widyaningsih; Dwi Nur Aini; Ni Komang Ayu (LPPM STIKES Guna Bangsa, 2018)
Background: Diarrhea is an increase in the number, frequency,and fluidity (level of dilution) of feces.Diarrhea can be acute and chronic. Chronic diarrhea is usually caused by chronic conditions, such as lactose intolerance. Early formula feeding can cause diarrhea in infants. Phenomena that occurred in Dahlia Room RSUD Dr. H. Soewondo Kendal is a lot of moms give formula milk to their baby and have diarrhea. This research aims to the relationship of formula feeding with diarrhea occurrence in infants. Method: The type of research is quantitative with cross sectional approach with accidental sampling sampling technique conducted on 26 mother giving formula milk and diarrhea in Juli 2017. Data collection using formula feeding questionnaire with diarrhea occurrence. Results: The results showed that 14 respondents 53.8% and high formula feeding were 12 respondent (42,6%). Responden with chronic diarrhea cases were 14 respondent (53,8%) and the incidence of acute diarrhea was 12 respondent (42,6%). The result of statistical test using chi square test with α = 0,05 is found that relationship between formula feeding with diarrhea occurrence in Dahlia Room RSUD Dr. H. Soewondo Kendal (p value = 0,045) with value X2 = 4,013. Conclusion: There is a significant relationship between formula feeding and the incidence of diarrhea in the dahlia room RSUD Dr. H. Soewond Kendal. Suggestion: Mother of a baby aged 0-6 months in Dahlia Room RSUD Dr. H. Soewondo Kendal, is expected to provide exclusive ASI without other complementary food.